2018
DOI: 10.1159/000494019
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Seasonality in Hemodialysis Patients from Five European Cities of Different Latitudes

Abstract: Background/Aims: Climate influences the regulation of blood pressure (BP). Our objective was to precisely estimate BP seasonality in hemodialysis (HD) patients from five European cities with marked climate differences. Methods: Stable prevalent HD patients from 5 European facilities (Santa Cruz de Tenerife (Spain), Seville (Spain), Montpellier (France), Ottignies (Belgium), Umea (Sweden)) present over the years 1995-1999 were included in this historical longitudinal observational study. Individual monthly aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Although the scientific literature has demonstrated the inverse relationship between air temperature and blood pressure [ 34 ] for patients who are not undergoing hemodialysis [ 3 , 35 , 36 , 37 , 38 ] and patients undergoing hemodialysis [ 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 39 , 40 ], the quantification of this relationship using mixed-effect models adjusted in a longitudinal study has not been demonstrated for hemodialysis patients in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the scientific literature has demonstrated the inverse relationship between air temperature and blood pressure [ 34 ] for patients who are not undergoing hemodialysis [ 3 , 35 , 36 , 37 , 38 ] and patients undergoing hemodialysis [ 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 39 , 40 ], the quantification of this relationship using mixed-effect models adjusted in a longitudinal study has not been demonstrated for hemodialysis patients in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between air temperature and blood pressure has been established, the mechanisms underlying this relationship have not been fully understood to date, and there are likely to be multiple [ 6 , 23 , 38 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESKD population has been suggested to exhibit seasonal rhythms in several clinical parameters and morbidity/mortality rates (4,5,7,8). Cardiovascular event rates are higher in patients on hemodialysis (HD) in winter versus summer months and associate with fluctuations in BPs (5,(9)(10)(11). Interdialytic weight gain (IDWG) is higher in winter as well, suggesting a potential relationship with fluid status and BP (5).…”
Section: Introductionmentioning
confidence: 99%
“…Climate variables, such as maximum daily wind speed, maximum hourly range of temperature, and the maximum hourly range of barometric pressure, have been reported to be associated with a variety of diseases and symptoms, including blood pressure [12,13,14], cardiovascular disease [15,16], heatstroke [17], stroke [18], pediatric trauma [19], mortality [20], asthma [21,22], depression [23,24], rheumatoid arthritis [25,26], and pain in general [27]. Associations with climate variables have also been reported in the dental field for conditions such as temporomandibular disorders [28] and oral pain [29].…”
Section: Introductionmentioning
confidence: 99%